Micropropagation of asparagus officinalis L. (Garden Asparagus) in vitro - Nor Azlina Hasbullah (Tanjong Malim, 2019)
Micropropagation of asparagus officinalis L. (Garden Asparagus) in vitro by Nor Azlina Hasbullah